The impact of workington industrial effluent on the surface water quality of marimba river, Harare, Zimbabwe - Mutasa, Nyasha (Midlands State University, 2017)
Pollution of water bodies due to human activities such as industrial waste disposal is a serious challenge facing most developing countries in the world today. Thus the management and supply of freshwater to the public is compromised and the ecological integrity of these rivers is lost due to adverse impacts such as eutrophicaton with algal blooms proliferating in these rivers. This could be due to such factors as pre-treatment costs, costs of having pre-treatment plants and ineffective and irregular monitoring of companies by responsible authorities. This study is an analysis of the effects of industrial effluent from Workington Industrial effluent on the water quality of Marimba River. Workington Industrial Area consists of such companies as Omnia and Windmill fertiliser companies, Exide Battery Company and ZESA. The study aimed at analysing the following water quality parameters which are BOD5, COD, phosphates, nitrates, lead, copper, temperature, pH and Pv4hr. The effluent was also measured against the EMA industrial effluent discharge limits. Samples were taken upstream of the river, about 3.22 km from discharge point, in the storm drain, about 3.05 km from discharge point and downstream 4.39 km away from discharge point. The upstream of the river was taken as the control .Result from the study showed that there was high nutrient loading of the river in the effluent from the industries with phosphates (4.67 mg/l), nitrates (5.31mg/l), which also lead to high oxygen demand of BOD (85.72 mg/l), COD (101.1 mg/l) and Pv4hr of (12.95mg/l). Recommendations are that there should be effective and regular monitoring of the area by the responsible authorities and also regular river monitoring.